Tracing Gender Equality in Restrictions on Female Teachers' Teaching Roles in Pesantren - M. Sahal Mahfudh; Istiadah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study aims to reveal the existence of gender inequality in the implementation of education in pesantren because there is a phenomenon in the form of pesantren regulations that limit the teaching role of female teachers, especially female teachers are prohibited from teaching in male student classes. This restriction of teaching roles creates the impression that pesantren have marginalised the role of female teachers. Considering the negative impression on pesantren institutions due to this phenomenon, this issue needs to be explored more deeply, especially from the perspective of the pesantren teachers themselves who are assumed to be marginalised in their roles. This study observed the above phenomenon by exploring the opinions of teachers in pesantrens using a qualitative approach through questionnaire instruments and in-depth interviews. The sample size for the questionnaire instrument in this study was 70 pesantren teachers consisting of 35 female teachers and 35 male teachers, while in-depth interviews were conducted with 3 teachers. The results revealed that these restrictions cannot be rashly claimed as a form of regulatory policy that is not gender fair. This is because the data obtained shows that the majority of pesantren teachers, both male and female, agree with the restrictions with various reasons and arguments.